Using historical aerial photography for monitoring of environment changes: a case study of Bovan Lake, Eastern Serbia - Bakrač, Saša; Marković, Viktor; Drobnjak, Siniša; Đorđević, Dejan; Stamenković, Nikola (Journal of Environmental Engineering and Landscape Management, 2021)
Useful and important information for the spatial, ecological, and many other changes in the living environment may be obtained using the analysis of historical aerial photography, with comparison to contemporary imagery. This method provides the ability to determine the state of elements of the space over a long period, encompassing the time when it was not possible to acquire the data from satellite imagery or some other contemporary sources. Aerial images are suitable for mapping spatial phenomena with relatively limited spatial distribution because they possess a high level of details and low spatial coverage. With a comparative analysis of aerial imagery from the past, contemporary aerial imagery, and other sources of aerial imagery, we can obtain information about the nature and trends of the observed phenomena as well as directions of future actions, considering changes detected in the environment, whether they are preventive or corrective in nature. This paper gives the methodological framework for the appliance of the existing knowledge from various fields, intending to use historical aerial photography for monitoring of environmental changes of the Bovan Lake in Eastern Serbia.